Komodifikasi Kedukaan Keluarga Brigadir J Dalam Talk Show Rosi di Kompas TV - Bonardo Marulitua Aritonang (Prisani Cendekia Institute, 2023)
Television as an agent of capitalism produces a variety of programs that are able to